Effect of Aerobic Composting on Some Environmental Health Parameters - Topal, E. Isil Arslan; Topal, Murat; Obek, Erdal; Ipek, Ubeyde; Baykara, Oktay (Gazi Univ, 2010)
Environmental health properties such as total coliform (TC), fecal coliform (FC) and heavy metals were investigated during composting of Marketplace Waste (MW) and the changes in radioactivity were investigated in raw and stabile composts. The number of coliforms decreased during composting and the composts obtained in this study had heavy metals under the standards. Alpha and beta radioactivity levels decreased. The concentrations of K-40 and Cs-137 were determined. The results obtained from the investigated parameters showed that the risk for human health could not arise during the usage of these composts in soil.
Keywords: Waste; health; composting; radioactivity; heavy metals; indicator bacteria